Nonlocal charges for bonus yangian symmetries of Super-Yang-Mills - Berkovits, Nathan [UNESP]; Mikhailov, Andrei [UNESP] (Springer, 2011)
The existence of a "bonus" U(1) level- one Yangian symmetry of N= 4 superYang- Mills has recently been proposed. We provide evidence for this proposal by constructing the BRST-invariant nonlocal charge in the pure spinor sigma model corresponding to this bonus level-one symmetry. We also construct analogous charges for bonus U(1) symmetries at all odd levels of the Yangian.
Keywords: AdS-CFT Correspondence; Integrable Field Theories